The temporomandibular joint of California sea lions (Zalophus californianus): Part 2-osteoarthritic changes. Issue 1 (January 2015) - Arzi, B.; Leale, D.M.; Sinai, N.L.; Kass, P.H.; Lin, A.; Verstraete, F.J.M.
Highlights We study the TMJ of California sea lions in a museum collection of skull specimens. California sea lions have high occurrence (63.5%) of osteoarthritis of the TMJ. There is no association between age and sex with the presence or severity of TMJ-OA. TMJ-OA is present at the mandibular head and affects the entire articular surface. The high incidence of TMJ-OA is likely to affect morbidity and mortality.